ANALISIS PARAMETER OSEANOGRAFI UNTUK PENENTUAN HABITAT IKAN PELAGIS DI PERAIRAN PAPARAN SUNDA - Mutiara R. Putri; Fitri Suciaty (Jurnal Perikanan Universitas Gadjah Mada, 2010)
In order to determine the regions in the Indonesia waters that are suitable for small pelagic fish habitat, analysis of net primary productivity (NPP) that is associated with oceanographic conditions has been carried out in this study. The NPP values derived from satellite data were calculated using the Vertically Generalized Productivity Model (VGPM). Meanwhile, the oceanographic conditions which are represented by temperature, salinity, and ocean currents were obtained by using a hydrodynamics numerical model. The result of this analysis was then compared with available acoustic observations. The results show that NPP in the Sunda Shelf Waters have different variations. The NPP along the southern coast of Kalimantan in the Java Sea and Centre Part of Malaka Strait around the Riau Waters always high throughout the year, i.e. more than 1000 mgC/m²/day and 750 mgC/m²/day, respectively. Variations in NPP values were strongly inﬂ uenced by seasonal variation of oceanographic conditions, which would physically affect the living habitat of pelagic fish in the Sunda Shelf. During the east monsoon, the salinity and temperature in the Eastern Java Sea and Makassar Strait were very suitable for pelagic fish, i.e. from 32 to 33 psu and 27 to 28°C, respectively. Meanwhile, during the east monsoon, the condition becomes less suitable. By contrast, in the Malaka and Karimata Straits, the oceanographic conditions during the west monsoon were more suitable, with almost similar mixed layer depth, i.e. 5 meters.